PRESENTATION OF MAXILLOFACIAL INJURIES IN THE 2005 EARTHQUAKE VICTIMS - Abbas, Iram; Abbasi, Masroor Manshad; Ghous, Shah Muhammad; Ahmad, Nofil; Ahmad, Ans; Ayub, Muhammad (Journal of Ayub Medical College Abbottabad, 2013)
Background: Earthquakes cause a lot of damage to life and property. Maxillofacial injuries constitute an important proportion of injuries in earthquakes and some 13% of the trauma patients after the earthquakes suffer from maxillofacial injuries. The objective of this study was to assess the presentation of maxillofacial injuries in earthquake victims. Methods: This descriptive study was conducted at the Department of Oral and Maxillofacial Surgery, Dental Section Ayub Teaching Hospital, Abbottabad from October 8th, 2005 to January 8th, 2006. Three hundred and seventy-eight patients were included in this study in the three months following the October 8th, 2005 earthquake on consecutive non-probability sampling basis. Results: Isolated facial bone fractures rather than the multiple bone fractures were the commonest type of fractures in earthquake victims. A significant number of patients presented with only soft tissue injuries and no bony fractures. Conclusion: Although considerable number of patients with fracture of multiple facial bones were present in the earthquake victims but isolated facial bone fractures and soft tissue injuries were the commonest type of injuries. Keywords: Earthquake, multiple facial bone fractures, isolated facial bone fractures